Classroom Environment and Pedagogical Practices as Determinants of Mathematics Anxiety in Senior High School: Evidence from Ghana - Comfort Azuuga; Paul Agmabire Akendita; Francis Abunkurug (EDUPEDIA Publisher, 2026)
Purpose - This study aimed at examining the role of classroom management practices, which include classroom structures, instructional strategies, and classroom practices by teachers as determinants in reducing the level of mathematics anxiety among students in Senior High school in the Upper East Region of Ghana. Methodology - A descriptive survey design was adopted under a quantitative approach. A purposive sample of 200 senior high school students with identified mathematics anxiety in the Upper East Region of Ghana participated in the study. Data were collected via structured questionnaires, and hypotheses were tested using chi-square analysis in SPSS Findings - The results indicated a strong correlation between the use of classroom management practices and a low rate of mathematics anxiety in students. In particular, the physical classroom set-up, teaching methods used by mathematics teachers, and the pedagogical practices of the teachers were also discovered to have played a significant role in determining the level of mathematics anxiety among students. Novelty - This is the first study because it empirically looks at classroom management practices as a measure to curb mathematics anxiety in the context of the Senior High School in the Upper East Region of Ghana. Compared with previous research, which primarily involves cognitive or curricular conditions, this research yields new information on how classroom organization and instructional practices by teachers can help to solve affective problems of students in mathematics. Significance - The study thus promotes the incorporation of effective classroom management practices in mathematics teaching and also gives a guide to future research on affective aspects in mathematics education.